WOLF WARRIOR DIPLOMACY CHINA TERHADAP AMERIKA SERIKAT MELALUI MEDIA SOSIAL DI ERA COVID-19 - Aziz, Aufarrifqi Muthahhari; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The bilateral relationship between the United States and China is peculiar, as they often exhibit hostility but occasionally cooperate for mutual interests, goals, and security. The Covid-19 pandemic has led to conflicts, with President Trump accusing China of being the virus spreader using terms like